EVAPOTRANSPIRATION, CROP COEFFICIENT AND SUGARCANE GROWTH PLANTED BY PRE-SPROUTED SEEDLINGS AND STALKS - Sandrini, Maria Eduarda Najm; Dalri, Alexandre Barcellos; Coelho, Anderson Prates; De Faria, Rogério Teixeira; Palaretti, Luiz Fabiano (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
Currently, the sugarcane presents several types of planting, especially the planting by pre-sprouted seedlings. This system needs new studies for the adequate recommendation of agronomic practices, such as irrigation. We aimed in this work to evaluate and compare the water consumption, crop coefficient and initial growth of sugarcane planted by pre-sprouted seedlings (PSS) and stalks. Four treatments were defined, being sugarcane planted by PSS and by stalks, bahiagrass grass and bare soil, all kept in weighing lysimeters. The reference evapotranspiration (ETo) was measured in the grass lysimeters. The crop evapotranspiration (ETc) of sugarcane planted by PSS and stalks was estimated by the water balance in the soil. The estimation of the crop coefficients (Kc) was obtained from the ratio between ETc of lysimeters with sugarcane and ETo. Comparison of the variables between planted sugarcane by PSS and by stalks was performed by regression analysis. The Kc of the sugarcane planted by stalks ranged between 0.86 to 2.88 and planting by PSS from 1.12 to 3.10. The sugarcane planted by PSS presents higher water consumption, crop coefficient and initial growth than when planted by stalks.
EVAPOTRANSPIRAÇÃO, COEFICIENTE DE CULTURA E CRESCIMENTO DE CANA-DE-AÇÚCAR PLANTADA POR MUDAS PRÉ-BROTADAS E POR TOLETES
Keywords: Arduino; Irrigation; Kc; Water consumption; Weighing lysimeter